1988
DOI: 10.1002/1097-0142(19880115)61:2<370::aid-cncr2820610228>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Primary lymphoma of the liver

Abstract: Nine adult white men ranging in age from 27 to 76 (mean, 55 years) were treated for primary hepatic lymphoma between 1972 and 1986 at the Memorial Sloan-Kettering Cancer Center. Six patients presented with right upper quadrant or epigastric pain or discomfort, and three patients complained of fatigue and lethargy. Fever and night sweats were evident in two, and two patients had lost weight. One patient was asymptomatic; the liver mass was detected during the work-up for cancer of the prostate. Seven patients o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(51 citation statements)
references
References 17 publications
3
48
0
Order By: Relevance
“…Hodgkin's disease occurs more often as miliary lesions than masses: Early in the disease liver parenchyma involvement is microscopic, but with time, small nodules from a few millimeters to several centimeters in size develop. In non-Hodgkin's lymphoma, the lymphocytic form tends to be miliary, whereas the large cells or histiocytic varieties are nodular masses [81,82].…”
Section: Lymphomamentioning
confidence: 77%
“…Hodgkin's disease occurs more often as miliary lesions than masses: Early in the disease liver parenchyma involvement is microscopic, but with time, small nodules from a few millimeters to several centimeters in size develop. In non-Hodgkin's lymphoma, the lymphocytic form tends to be miliary, whereas the large cells or histiocytic varieties are nodular masses [81,82].…”
Section: Lymphomamentioning
confidence: 77%
“…[25,26] Secondary hepatic lymphomas are defined by some authors as liver lymphomas with extra hepatic foci of lymphoma and found at the first onset or afterwards, or systemic lymphoma with secondary hepatic involvement. This description is also conflicting with the above definition of primary lymphoma.…”
Section: Classification Of Lymphomamentioning
confidence: 99%
“…The frequency of elevated liver enzymes has been reported to be 7.5 to 26.0% among patients treated with MTX (28,29), and ALT is a representative marker of MTXrelated hepatotoxicity (30,31). On the other hand, the AST, LDH and ALP levels are elevated in many PHL patients (32). The present patient also demonstrated elevation of AST, LDH and ALP.…”
Section: Discussionmentioning
confidence: 99%